Geopolitical Landscape of South Asia and Doctrinal Evolution in India under Modi Era (2014-2024) - Hina Butt; Muhammad Salman; Dr. Muhammad Umer Hayat (Journal of Quranic and Social Studies, 2025)
During Prime Minister Narendra Modi's era (2014–2024), India's doctrinal change reiterates the denunciation of defensive deterrence and embraces proactive military involvement in aspiration for becoming Asia Tiger. This paper studies the pattern of strategic recalibration of India owing to China's military ambition, India's proxy warfare, strategic defense partnership with the US, aggressive strategic relations with Pakistan, and regional turmoil in South Asia. It would be India's institutionalization of Integrated Battle Groups (IBGs), adoption of the New Land Warfare Doctrine (2018), use of surgical strikes (2016 Uri, 2019 Balakot), and willingness to engage in preemptive deterrence, force projection, and denial strategy that speak volumes, indicating India's readiness for military deterrence and campaigns. Additionally, India has broadened the definition of hybrid warfare, with the conflation of cyber operations, information warfare, and economic statecraft to respond to conventional and non-conventional threats. Establishing the Chief of Defence Staff (CDS) and tri-services theater commands has enhanced joint military coordination. This paper analyzes interplay between regional security dynamics and India's doctrinal transformation during Modi’s era. Current study is qualitative in approach based on archival data under the theoretical lens of offensive realism. India’s strategic policies and aspirations for regional leadership in Indo-Pacific are escalating tension against Pakistan and China. This paper offers an in-depth study analysis of India's doctrinal shifts, geopolitical motifs, and its broader bearings on the trajectory of global security.